Organ motion quantification and margins evaluation in carbon ion therapy of abdominal lesions. (July 2020) - Kalantzopoulos, Charalampos; Meschini, Giorgia; Paganelli, Chiara; Fontana, Giulia; Vai, Alessandro; Preda, Lorenzo; Vitolo, Viviana; Valvo, Francesca; Baroni, Guido
Highlights: 2DcineMRI estimates tumour motion in carbon ion therapy of abdominal site. The estimated motion from cineMRI and 4DCT are significant different. Tumor margins built on cineMRI were compared to the clinical margin. The clinical margin was not significant different from the cineMRI one for gating. Gating treatment is robust to inter-fraction and intra-fraction motion. Abstract: Purpose: In image-guided particle radiotherapy of abdominal lesions, respiratory motion hinders treatment accuracy. In this study, 2D cineMRI data were used to quantify the tumor (GTV) motion and to evaluate the clinical approach based on deriving an internal target volume (ITV) from a planning 4DCT for gating treatments. Methods: Seven patients with abdominal lesions were treated with carbon-ion therapy at the National Centre of Oncological Hadron-therapy (Italy). The MR scan was performed on the same day of the 4DCT acquisition. For four patients, an additional MR was acquired approximately after 1 week. The cineMRI combined with deformable image registration algorithm was used to quantify tumor motion. Afterwards, two ITVs were defined considering (1) all phases (ITVFB ) and (2) only phases within the gating window (ITVG ), and then compared with the clinical (4DCT-derived) ITVs (ITVCG and ITVCFB ). Results: Tumor residual motion estimated by cineMRI data in the two MRI sessions resulted not significantly different from 4DCT, although cineMRI accounted for cycle-to-cycle variations. The ITV normalized for the GTV median values were higher for ITVFB with respect to ITVG, ITVCFB and ITVCG . The Hausdorff distances with respect to the GTV were up to 10.55 mm, 3.13 mm, 5.56 mm and 2.51 mm, for ITVFB, ITVG, ITVCFB and ITVCG, respectively. According to both metrics, ITVCG and ITVG were not found significantly different. Conclusions: CineMRI acquisitions allowed to quantify organ motion without delivering additional dose to the patient and to verify treatment margins in gated carbon-ion therapy of abdominal lesions.